Analisis Strategi Harga dan Medsos Terhadap Minat Berkunjung Di Taman Purbakala Palembang - Fajar, Muhamad; Widagdo, Herry (MDP Student Conference, 2024)
The purpose of this research is to determine the analysis of pricing and social media strategies on visiting interest Taman Purbakala Kerajaan Sriwijaya Palembang. Collecting data for this research distributed questionnaires to 230 respondents. Utilising a purposive sampling technique and nonprobability sampling, SPSS 23 was employed for the sampling process. With a value of 0.000 < 0.05, the partial test findings indicated that Prices and social media had a significant positive impact on interest in visiting. The results of the simultaneous test demonstrate that the prices and social media variables have a positive and significant impact on visitors' interest in visiting, with a F value of 672.771 and a significant value of 0.000.